PELATIHAN PEMBUATAN MEDIA KEYAKINAN KELAS SEBAGAI PENERAPAN DISIPLIN POSITIF GURU JENJANG SMP DI MOJOKERTO - Rahayuningsih, Suesthi; Mardliyah, Asih Andriyati; Rijanto, Achmad (Universitas Mataram, 2024)
his training activity was part of the Community Partnership Empowerment activity. This activity was carried out in partnership with SMP Negeri 2 Puri which was located in Mojokerto district, East Java province. Mitra was about 9 kilometers from the Majapahit Islamic University. The background for implementing this training is due to the lack of teacher knowledge and skills regarding the practice of creating classroom belief media as an application of positive discipline in schools. This has the effect of not having class confidence in implementing positive discipline in each class, so that positive discipline values ​​cannot be implemented properly by students in each class. The aim of this training was to provide knowledge and skills to teachers so that they can create classroom confidence media in each class, so that classroom confidence media was available in every class carried out by students, in order to achieve the application of positive discipline in each class. The method of activity carried out was to provide material on how to create class confidence media in implementing positive discipline to teachers, as well as examples of its application in schools. The results of this training activity are that based on the results of the initial tests that have been carried out, the average score for teacher knowledge regarding creating class confidence media for implementing positive discipline was 57.0 and teacher skills were 48.0. And based on the final test results, the average knowledge score was 93.0 and skills was 87.8. From this activity, it can be concluded that there was an increase in the average value of teacher knowledge regarding creating class confidence media for implementing positive discipline by 65.7% and skills by 86.4%.